Semantic Ambiguity and Its Impact on Language Interpretation in Legal Discourse - Sara Stefani Malau; Bernieke Anggita Ristia Damanik (Young Journal of Social Sciences and Humanities, 2025)
Semantic ambiguity remains a critical challenge in both linguistic theory and practical applications, especially in domains demanding high interpretive precision such as legal discourse. This study aims to examine the nature, sources, and implications of semantic ambiguity by integrating perspectives from cognitive linguistics, legal hermeneutics, and cross-cultural pragmatics. Employing a qualitative analytical method, data were drawn from legal case studies, discourse analysis, and comparative linguistic literature. The findings reveal that ambiguity often arises from polysemy, syntactic complexity, cultural frameworks, and pragmatic inference. In legal contexts, such ambiguity can significantly influence judicial outcomes and the interpretation of statutes. The study suggests that applying systematic semantic analysis and interdisciplinary interpretive models can minimize misinterpretation and promote fairness in communication. These results contribute to advancing theoretical insights in meaning studies while offering practical strategies for mitigating ambiguity in critical decision-making contexts.